2005
DOI: 10.1088/0967-3334/26/5/020
|View full text |Cite
|
Sign up to set email alerts
|

What affects esophageal injury during radiofrequency ablation of the left atrium? An engineering study based on finite-element analysis

Abstract: Recent studies on intraoperative radiofrequency ablation of atrial fibrillation have reported some cases of injury to the esophagus. The aim of this study was to perform computer simulations using a theoretical model in order to investigate the effect of different factors on the temperature distributions in the esophagus during ablation. A three-dimensional model was built to include an active electrode, atrial tissue, epicardial fat layer and a fragment of esophagus, aorta and lung, all linked by connective t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 27 publications
2
55
0
2
Order By: Relevance
“…[11][12][13] A major limitation of this approach is that it fails to account for the variability in the thickness of the posterior LA wall and the presence of periesophageal connective tissue-important determinants of esophageal heating. 7,14,15 Thus, empirically limiting the power and duration of RF applications may be insufficient to prevent esophageal thermal injury in all patients. The aim of this study was to determine whether RF power delivery during AF ablation guided by luminal esophageal temperature (LET) monitoring is associated with less frequent esophageal injury compared with a strategy of power limitation alone.…”
Section: Editorial See P 150 Clinical Perspective See P 168mentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] A major limitation of this approach is that it fails to account for the variability in the thickness of the posterior LA wall and the presence of periesophageal connective tissue-important determinants of esophageal heating. 7,14,15 Thus, empirically limiting the power and duration of RF applications may be insufficient to prevent esophageal thermal injury in all patients. The aim of this study was to determine whether RF power delivery during AF ablation guided by luminal esophageal temperature (LET) monitoring is associated with less frequent esophageal injury compared with a strategy of power limitation alone.…”
Section: Editorial See P 150 Clinical Perspective See P 168mentioning
confidence: 99%
“…Fourth, the distance between the left atria and the esophagus was not accounted for in this analysis. Although the total tissue thickness between the esophagus and LA is an important factor determining esophageal injury, 15 computed tomography analyses have suggested a close relationship of the posterior LA and esophagus in virtually all patients. 23 Moreover, adjusting for patient's body mass index did not result in any additional protection from esophageal ulceration.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Kardiyak aritmi, özellikle atrial fibrilasyon tedavisinde yapılan sol atrial radyofrekans (RF) ablasyonun özofa-gus hasarına yol açabildiği gösterilmiştir (15,16).…”
Section: İntraluminal Yaralanmalar 1 Enstrümental Yaralanmalarunclassified
“…4 Importantly, animal models suggest that these esophageal lesions are a form of thermal injury in that there is a linear relationship between the measured esophageal temperature and the frequency with which esophageal (and periesophageal) injury occurs as well as the size of individual lesions. 9,10 Over the past several years, investigators have reported on the merits of various intraprocedural interventions aimed at reducing the likelihood of inadvertent esophageal injury and thus an A-E fistula. These include some basic measures like reduction of energy when targeting the posterior LA wall or avoidance of lesions in this region and also techniques for real-time intraprocedural visualization of the esophagus, 11 11,13 monitoring the esophageal temperature during ablation using an intraluminal temperature probe, 7,11,14,15 cooling the esophagus during ablation, 16 and displacing the esophagus away from the site(s) of ablation.…”
Section: Editorial Commentmentioning
confidence: 99%